The special features of the content of discipline in NAU - Kuznetsova, I. (Theory and practice of design, 2016)
The special features of the content of discipline “Form-building Basics”, taught at National Aviation University, were brought to life by peculiarities of education in the university of a profile; with licensed specialties in the field of design, taking into account students’ habits of percepting the related subjects afforded; and, finally, they depend on the year and the student’s body, subject to studying the course. The topics are concerned gradually with perception of the image on the flat, with regard to its further spatial development; the transfer from the two-dimensional vision to perceiving the relief sculpture on the separate object surface; as well as development of spatial vision while constructing the shape of the object possessing the artistic image.